2018
DOI: 10.1158/0008-5472.can-17-3993
|View full text |Cite
|
Sign up to set email alerts
|

Licofelone Enhances the Efficacy of Paclitaxel in Ovarian Cancer by Reversing Drug Resistance and Tumor Stem-like Properties

Abstract: Drug development for first-line treatment of epithelial ovarian cancer (EOC) has been stagnant for almost three decades. Traditional cell culture methods for primary drug screening do not always accurately reflect clinical disease. To overcome this barrier, we grew a panel of EOC cell lines in three-dimensional (3D) cell cultures to form multicellular tumor spheroids (MCTS). We characterized these MCTS for molecular and cellular features of EOC and performed a comparative screen with cells grown using two-dime… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 53 publications
4
37
0
3
Order By: Relevance
“…The two-dimensional (2D) cancer cell cultures are restricted in serving as adequate models for drug screening and drug development [1,2] , due to challenges associated with for example, hypersensitivity to anti-cancer drugs [3] , and inability to recapitulate the complex intricate interactions within a tumor microenvironment (TME) [4] . The TME is capable of acting as both a potential barrier and facilitator of tumor proliferation by affecting various processes including local growth resistance, immune system interactions, and the formation of distant metastases [5] .…”
mentioning
confidence: 99%
“…The two-dimensional (2D) cancer cell cultures are restricted in serving as adequate models for drug screening and drug development [1,2] , due to challenges associated with for example, hypersensitivity to anti-cancer drugs [3] , and inability to recapitulate the complex intricate interactions within a tumor microenvironment (TME) [4] . The TME is capable of acting as both a potential barrier and facilitator of tumor proliferation by affecting various processes including local growth resistance, immune system interactions, and the formation of distant metastases [5] .…”
mentioning
confidence: 99%
“…Previous studies have shown that cancer cells resisting apoptosis in nonadherent conditions are also more chemoresistant (Eguchi et al, 2015; Foley et al, 2015; Wheeler et al, 2018). Additionally in ovarian cancer, nonadherent cancer spheroids either created in vitro or isolated from in vivo ascites fluid also demonstrate enhanced chemoresistance (Hirst et al, 2018; Liao et al, 2014; Wheeler et al, 2018). Moreover, ovarian cancer spheroids are thought to be a unique subpopulation of tumor cells with self‐renewal capability and enhanced chemoresistance (Liao et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…The screening of FDA-approved library is an interesting technique already used in different fields by researchers (26,27). Indeed, by examining all the drug classes on the same cellular model it is possible to find new applications for an old drug and, hence, introduce an already existing therapy to a new disease, the so called drug repurposing (28). In addition, drug repurposing allows rapid clinical impact and patient benefit at reduced cost and time requirements than de novo drug development as a result of the availability of bioactivity and safety data from clinical trials for each compound used in the screening (21).…”
Section: Discussionmentioning
confidence: 99%